Immune Dysregulation after Cardiothoracic Surgery and Incidental Thymectomy: Maintenance of Regulatory T Cells despite Impaired Thymopoiesis - Nancy J. Halnon; Paige Cooper; Diana Yu Hui Chen; M. Ines Boechat; Christel H. Uittenbogaart (Clinical and Developmental Immunology)
Thymectomy is performed in infants during cardiothoracic surgery leaving many patients with reduced thympopoiesis. An association between immune disorders and regulatory T cells (Treg) after incidental thymectomy has not been investigated. Questionnaires soliciting symptoms of atopic or autoimmune disease and biomarkers were measured in children and adults with congenital heart disease and either reduced or preserved thymopoiesis. Tregs were examined. Atopic or autoimmune-like symptoms and elevated anti-dsDNA antibodies were common after surgery in individuals with low thymopoiesis. Total Treg number and function were maintained but with fewer naïve Treg. TCR spectratypes were similar to other memory T cells. These data suggest that thymectomy does not reduce total Treg number but homeostasis is affected with reduced naïve Treg. Prevalence of autoimmune or atopic symptoms after surgery is not associated with total number or proportion of Tregs but appears to be due to otherwise unknown factors that may include altered Treg homeostasis.